ANALISIS PAJAK RESTORAN TERHADAP PENINGKATAN PENDAPATAN ASLI DAERAH KOTA PADANG PANJANG - Nurfitriyenny, Nurfitriyenny; Muslim, Muslim; Supryanita, Rina; Rahmawaty, Dian; Fitria, Fitria (Media Mahardhika, 2024)
This research aims to analyze the effectiveness of restaurant taxes and the contribution of restaurant taxes to increasing local revenue in the city of Padang Panjang. In this research using quantitative and qualitative analysismethods. The results of the research conducted suggest that the effectiveness of restaurant tax collection for 2017-2021 is quite effective, with an average effectiveness rate of 89.05%. The highest percentage of effectiveness wasin 2021 at 98.13% and the lowest in 2018 was 81.21%. Meanwhile, the contribution of restaurant tax in 2017-2021was very less, with an average contribution of 1.30%, the highest contribution in 2018 is 1.53% and the lowest in2020 was 1.18%.